Performance improvement of gas-driven absorption heat pumps by controlling the flow rate in the solution branch. (January 2023) - Villa, Giorgio; Toppi, Tommaso; Aprile, Marcello; Motta, Mario
Highlights: Seasonal performances of gas-driven NH3 -H2 O absorption heat pumps are compared. Single effect, Generator Absorber eXchange, and Vapor cycles are considered. Fixed, double, and variable restrictors in the solution branch are considered. The use of variable restrictors increases the seasonal gas utilization efficiency. Performances increase up to 12%, especially for the advanced cycles (GAX and VX). Abstract: Gas-driven absorption heat pumps are a valid alternative to condensing boilers for non-insulated buildings with radiators as emission system. In fact, they can provide high supply water temperatures with limited performance degradation. However, their seasonal performance is often limited by suboptimal operation at partial load conditions, due to the reduced generator temperature. In this paper, the use of variable and double restrictor on the solution branch between generator and absorber are investigated as possible options to optimize the generator temperature at different operating conditions. The seasonal gas utilization efficiency (SGUE) of three different absorption cycles is compared through numerical simulations using the approach proposed by the standard EN12309. The considered cycles are the single effect cycle (SE), the Generator-Absorber eXchange cycle (GAX), and a version of the Vapor eXchange cycle (VX). Results show that the use of a double restrictor provides an improvement of the SGUE of 7% for the VX cycle, 6% for the GAX cycle and 2% for the SE cycle, compared to the classic fixed restrictor cases. The variable restrictor provides an increase of the SGUE of 12%, 10%, and 2.3% for VX cycle, GAX cycle, and SE cycle respectively. The variable restrictor provides the best performances because it can optimize the generator temperature for every working condition, while the double restrictor gives remarkable improvements with a simpler and easier to be controlled approach. Advanced cycles obtain the highest performance improvements because an appropriate temperature in the generator is of paramount importance for their correct operation.